2021
DOI: 10.14744/ijmb.2021.65477
|View full text |Cite
|
Sign up to set email alerts
|

Association of HBA gene copy number gains with pathogenic HBB gene variants

Abstract: 8]. Four alleles of 2 structurally similar genes, HBA1 and HBA2 are responsible for α-globin gene expression and are critically important when establishing genotype-phenotype relationships in patients with β-thalassemia. Although the HBA1 gene Objectives: Alpha (α) and beta (β) thalassemia are the most prevalent genetic hematological disorders. The co-occurrence of silent β-thalassemia with excess α-globin gene copies is associated with the thalassemia intermedia phenotype. This study was an investigation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…From the age of 6 months, HbA is the predominant type of hemoglobin in humans and accounts for 95-98% of the total hemoglobin molecules [43]. Simllar to our study finding, a previous investigation showed a signifcant decrease in HbA level in thalassemia patients [44]. Low HbA levels were related to a decline in physical function in beta-thalassemia patients, which was associated with elevated IL-6 levels [45].…”
Section: Discussionsupporting
confidence: 76%
“…From the age of 6 months, HbA is the predominant type of hemoglobin in humans and accounts for 95-98% of the total hemoglobin molecules [43]. Simllar to our study finding, a previous investigation showed a signifcant decrease in HbA level in thalassemia patients [44]. Low HbA levels were related to a decline in physical function in beta-thalassemia patients, which was associated with elevated IL-6 levels [45].…”
Section: Discussionsupporting
confidence: 76%